2011
DOI: 10.1017/s1751731111000255
|View full text |Cite
|
Sign up to set email alerts
|

Influence of digital dermatitis and sole ulcer on dairy cow behaviour and milk production

Abstract: The aim of the study was to investigate whether the presence of digital dermatitis (DD) and sole ulcer (SU) in dairy cows was associated with changes in behaviour and milk production. Swedish Red and Swedish Holstein cows (mostly in the first to second lactation) were housed in a cubicle system with automatically scraped passageways. After maintenance claw trimming of all the cows in the herd, 10 cows with DD and 10 cows with SU were selected. For each DD-or SU-affected cow, a healthy control cow, matched acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 34 publications
1
32
2
1
Order By: Relevance
“…However, HULTGREN et al (2004) found no relationship between lameness and udder health, and observed that only severe lameness impairs the cows' movements and increases the risk of teat injuries and subsequent mastitis. Contrary to the results of the above studies, ARCHER et al (2011) andPAVLENKO et al (2011) found a negative association between locomotion score and milk SCC. Lame cows were found to have lower milk SCC than non-lame cows, due to increased standing time in lame cows, causing the udders to be less exposed to intra-mammary infections.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, HULTGREN et al (2004) found no relationship between lameness and udder health, and observed that only severe lameness impairs the cows' movements and increases the risk of teat injuries and subsequent mastitis. Contrary to the results of the above studies, ARCHER et al (2011) andPAVLENKO et al (2011) found a negative association between locomotion score and milk SCC. Lame cows were found to have lower milk SCC than non-lame cows, due to increased standing time in lame cows, causing the udders to be less exposed to intra-mammary infections.…”
Section: Resultscontrasting
confidence: 99%
“…In their successive trial, OLECHNOWICZ and JACEKOWSKI (2012) observed that clinical lame cows had significantly lower milk protein content as compared to healthy cows. Similarly, no change in milk composition was recorded between healthy, digital dermatitis affected cows and sole ulcers affected cows in a recent study (PAVLENKO et al, 2011).…”
Section: Resultsmentioning
confidence: 74%
“…Other factor which might explain our results is the short period of seven days between the first and the last behavioral measurement. González et al (2008) reported that lame cows showed a tendency to increase daily feeding time and average meal duration within 30 days after treatment, while Pavlenko et al (2011) noticed differences in the ingestive behavior between lame and healthy cows two to three weeks after trimming and treatment. The similarity in rumination time is a consequence of similar eating times and composition of diet, as rumination is closely related to the amount and effectiveness of fiber ingested (Park et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of that, Chapinal et al (2009) found no differences in lying time for animals with digital dermatitis or sole ulcers when compared with animals without lesions. Controversy about lying time spent by lame cows might be due to the differences about how cows were housed and the periodicity of behavioral observations (Pavlenko et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To point out the importance of reducing the presence and severity of foot disorders, advice should include information about the scale of the problem and the consequences in terms of economics and animal welfare. Different intervention measures can be -E-mail: Marielle.Bruijnis@wur.nl taken to improve dairy cow foot health, such as improvement of the flooring (Vanegas et al, 2006), lying surface (Cook and Nordlund, 2009) and hygiene (Somers et al, 2005b), but also regular checking and trimming (Pavlenko et al, 2011). Each measure has its own effect on foot disorders.…”
Section: Introductionmentioning
confidence: 99%